How to read and understand a research study - Farrar, LAuren; Stern, Nimmers; Insight Media (firm) (New York : Insight Media, 2008)
'Introducing the basic components of a research study, this program examines the ways in which research studies are reported and teaches how to read and understand them. It outlines the structure of a scientific paper, defines important terms, considers the information that statistics provide about the value of a study, and shows how to evaluate the quality of information presented in a research study.' --from publisher's website
Narrator: Jerry Goralnick
DVD format
Keywords: Research -- Evaluation; Research -- Methods